Efisiensi Ekonomi Usaha Gula Aren Serta Faktor Faktor Yang Berpengaruh Terhadap Pendapatannya di Kabupaten Garut - Suryo Arifianto, Dimas; Awaliyah, Fitri; Nu'man Adinasa, Muhamad (Universitas Garut, 2024)
Arenga pinnata Merr, or the sugar palm, is a high-value economic commodity from the Arecaceae family, whose success in development is highly influenced by the environment where it is cultivated. This study aims to assess the efficiency of the sugar palm processing business and identify the most influential factors, the results of which could serve as a foundation for policymakers and stakeholders in formulating policies to improve sugar palm business efficiency. The research uses a quantitative approach supported by qualitative interpretation, conducted in three sub-districts in Garut Regency: Cisewu, Bungbulang, and Pakenjeng, chosen through purposive sampling. Primary data was obtained through surveys, direct observation, and in-depth interviews with palm farmers, focus group discussions (FGD), while secondary data came from trusted sources, Agricultural Statistics, and scientific literature. Sampling was carried out using purposive sampling with 30 respondents. Data analysis employed descriptive statistics through several analytical methods, including Data Envelopment Analysis, Cost-Benefit Analysis, Economies of Scale, and Linear Regression Analysis. The DEA results show that the majority of sugar palm farmers (99.3%) are efficient, and 63.3% experience Economies of Scale, where costs per unit are low but production is maximal, indicating efficiency in operations. These results are also supported by a Cost-Benefit Ratio of 2.92. The factor significantly affecting income is the number of sugar palm trees owned, highlighting the importance of increasing productivity through tree addition. However, all respondents still rely on natural growth without organized seedling programs.